Karakteristik Uji Marshall Campuran Laston Asphalt Treated Base (ATB) Dengan Limbah Beton Sebagai Substitusi Bahan Agregat Kasar - Jannika Suhelmi; Muhammad Shalahuddin; Muhamad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Infrastructure boom requires a large amount of aggregate which is non renewable. On the other hand infrastructure construction create some amount of concrete waste which might be recycled. This study investigated marshall characteristic of Asphalt Treated Base using concrete waste as coarse aggregate substitution. Concrete waste was mixed with fresh aggregate at ratio of 100:0, 75:25, 50:50, 25:75 and 0:100 asphalt content varied are 5%, 5.5%, 6%, 6.5% and 7%. The optimum aggregate contents for each variation i.e. 6.05%, 6%, 6.5%, 6.5% and 6% respectively. The results show that all variation fulfilled the specification the 75:25 variation was recommended as mixture ratio with high stability value 2.320 kg and also asphalth content was affordable with 6% of optimum asphalt content.Keywords: Waste concrete, aggregate, asphalt treated base (ATB)